1975
DOI: 10.1002/cne.901610304
|View full text |Cite
|
Sign up to set email alerts
|

Human brain in tissue culture. III. PML‐SV40‐induced transformation of brain cells and establishment of permanent lines

Abstract: Cells from explants and monolayer subcultures of adult human brain obtained from biopsies or autopsies of ten multiple sclerosis (MS) cases, one case each of Jakob-Creutzfeld (JC) and amyotrophic lateral sclerosis (ALS) and three cases with no central nervous system (CNS) involvement were transformed with PML-SV40 virus. Transformation was effected to establish permanent lines of these particular adult brain cells so that sufficient quantities would be available for other research projects. The procedure previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1975
1975
1992
1992

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…JCV genomic DNA was prepared from the plasmid pJC (15) purified after BamHI and Hha I digestion, and passage over a Sephacryl S-1000 column (Pharmacia). The pSV2 vector was constructed by Mulligan and Berg (16) gin-defective mutant of SV40 (mutant [1][2][3][4][5][6][7][8][9][10][11] was provided by Y. Gluzman as an insert in the pMK16 vector at the BamHI site. All plasmids were grown in Escherichia coli K-12 hosts, amplified using chloramphenicol, and purified by a cleared lysis method (17,18).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…JCV genomic DNA was prepared from the plasmid pJC (15) purified after BamHI and Hha I digestion, and passage over a Sephacryl S-1000 column (Pharmacia). The pSV2 vector was constructed by Mulligan and Berg (16) gin-defective mutant of SV40 (mutant [1][2][3][4][5][6][7][8][9][10][11] was provided by Y. Gluzman as an insert in the pMK16 vector at the BamHI site. All plasmids were grown in Escherichia coli K-12 hosts, amplified using chloramphenicol, and purified by a cleared lysis method (17,18).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Miranda et al (8) have demonstrated that homogenous populations of human myoblast cells could be isolated from skeletal muscle cells after transformation with simian tumor virus 40 (SV40). Santoli et al (9) and Shein (10) have transformed human adult brain and fetal glial cells, respectively, using SV40. However, infectious SV40 was shed from these cells and, in the case of the fetal brain, the life span of the cells lasted only 13-39 cell passages.…”
mentioning
confidence: 99%
“…There have been reports that certain cells are more susceptible to SV40-induced transformation. In early studies it was claimed th at the likelihood of obtaining permanent lines increased with the age of the diploid culture (Jensen et al 1963), but this could not be confirmed by other investigators (Santoli et al 1975;Huschtscha & Holliday 1983). In comparison with normal cells, a consistent increase in the number of SV40-induced foci was reported in skin fibroblasts from patients with Fanconi's anaemia, which is a disease with a high incidence of chromosome abnormalities and spontaneous neoplasms (Todaro 1966 ;Todaro 1968).…”
Section: Introductionmentioning
confidence: 94%